Detection rate and predictive factors of sessile serrated polyps in an organised colorectal cancer screening programme with immunochemical faecal occult blood test: the EQuIPE study (Evaluating Quality Indicators of the Performance of Endoscopy). Issue 7 (19th February 2016) - Zorzi, Manuel; Senore, Carlo; Da Re, Filippo; Barca, Alessandra; Bonelli, Luigina Ada; Cannizzaro, Renato; de Pretis, Giovanni; Di Furia, Lucia; Di Giulio, Emilio; Mantellini, Paola; Naldoni, Carlo; Sassatelli, Romano; et al.
Abstract : Objectives: To assess detection rate and predictive factors of sessile serrated polyps (SSPs) in organised colorectal cancer (CRC) screening programmes based on the faecal immunochemical test (FIT). Design: Data from a case series of colonoscopies of FIT-positive subjects were provided by 44 Italian CRC screening programmes. Data on screening history, endoscopic procedure and histology results, and additional information on the endoscopy centre and the endoscopists were collected, including the age-standardised and sex-standardised adenoma detection rate (ADR) of the individual endoscopists. The SSP detection rate (SSP-DR) was assessed for the study population. To identify SSP-predictive factors, multilevel analyses were performed according to patient/centre/endoscopist characteristics. Results: We analysed 72 021 colonoscopies, of which 1295 presented with at least one SSP (SSP-DR 1.8%; 95% CI 1.7% to 1.9%). At the per-patient level, SSP-DR was associated with males (OR 1.35; 95% CI 1.17 to 1.54) and caecal intubation (OR 3.75; 95% CI 2.22 to 6.34), but not with the FIT round. The presence of at least one advanced adenoma was more frequent among subjects with SSPs than those without (OR 2.08; 95% CI 1.86 to 2.33). At the per-endoscopist level, SSP-DR was associated with ADR (third vs first ADR quartile: OR 1.55; 95% CI 1.03 to 2.35; fourth vs first quartile: OR 1.89; 95% CI 1.24 to 2.90). Conclusion: The low prevalence of SSPs and the lack of association with the FIT round argue against SSP as a suitable target for FIT-based organised programmes. Strict association of SSP-DR with the key colonoscopy quality indicators, namely caecal intubation rate and high ADR further marginalises the need for SSP-specific quality indicators in FIT-based programmes.